Anticancer Activity against Breast Cancer Cells T47D and Identification of Its Compound from Extracts and Fractions of Leaves Bamboo Grass (Lophaterum gracile B.) - Istiqomah, Alfi; Muti'ah, Roihatul; Hayati, Elok Kamilah (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2015)
Bamboo grass (Lophatherum gracile B.) is one of weed plants which frequently used as a medicine because it provides active compounds, for instance steroids and tannins. This research was conducted to determine the anticancer activity of extracts and fractions of leaves bamboo grass in inhibiting the growth of breast cancer cells T47D, and to determine the class of the active compounds contained in extracts and fractions which have the lowest IC50 value from phytochemical test and identification with UV-Vis instruments and FTIR. The extraction of active compound leaves of bamboo grass is done by maceration method using ethanol 80%, hydrolysis and partition with n-hexane and chloroform. Four of the extracts is phytochemical tested and anticancer activity tested towards breast cancer cells T47D with MTT method. The best results of the test activities are performed by the separation of classes of active compounds KLTP and are identified using UV-Vis spectrophotometer and FTIR. The value of IC50 from 80% ethanol extraction is 321,389, from hydrolysis extraction is 481.984, from the fraction of chloroform is 177.852, and from n-hexane fraction is 300.681 Âµg / mL. The lowest IC50 which have the best cytotoxic is the fraction of chloroform and n-hexane. The results of phytochemical test fractions of chloroform and n-hexane fraction indicates the tannin and steroids. The identification result by using UV-Vis and FTIR shows that the fraction of chloroform and n-hexane fraction is containing tannin, which isproven by maximum wavelength at 331.6 nm and 331.6 nm allegations of -OH, CH, C=C. Moreover, the existence of steroid compounds in fraction chloroform and n-hexane is shown by the absorption at 279.1 nm and 278.0 nm of wavelength with allegations of -OH, CH, C=C, C-O.